Implementasi Promotion Mix Pada Keluarga Baba Wedding Organizer Dalam Meningkatkan Jumlah Pengguna Jasa Di Era New Normal : Implementation of Promotion Mix in the Baba Wedding Organizer Family to Increase the Number of Service Users in the New Normal Era - Rifqi Farisi, Muhammad; Hadisiwi, Purwanti; Wirabhuana, Subekti P. (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
After experiencing a pandemic for approximately 2 years, many businesses, not only in Indonesia, but in the world began to strengthen their determination to bounce back. Not only did it cost lives due to exposure to Covid-19, but businesses also became victims. Nevertheless, there are also businesses that survive in the midst of this deadly virus attack which is full of uncertainty when it will end. The promotional mix is the best strategic combination of advertising variables, personal selling, and other promotional tools, all of which are planned to achieve the objectives of the sales programme. This research aims to find out how the implementation of the promotional mix at Keluarga Baba Wedding Organizer has managed to survive through a pandemic where the majority of business people have to go out of business due to hampered sales activities. The research method used in this research is the explanatory case study method. The informant determination technique used is purposive sampling technique. The result of this study shows that Keluarga Baba has implemented the promotion mix well, starting from the planning to the evaluation process. This is evident from the consistency of Keluarga Baba's educational-based advertising promotions on Instagram and the attractiveness of consumers who want to use Keluarga Baba's services.